A two-level strategy for simplification of fracture prediction in notched orthotropic samples with nonlinear behavior. (August 2022) - Hasaninia, Mohammad; Torabi, A.R.
Highlights: Fracture of notched nonlinear orthotropic samples is studied under mode I loading. Fracture tests are originally performed on U-notched Russian pine specimens. EMC and VIMC are employed simultaneously to simplify the complex material. MS and PS fracture models are applied to simplified material for NFT estimation. Both EMC-VIMC-MS and EMC-VIMC-PS mixed fracture models are shown to be successful. Abstract: In this paper, the load bearing capacity of U-notched specimens made of Russian pine wood, as a natural orthotropic material with nonlinear behavior, is investigated under pure mode I loading. The load bearing capacity of the orthotropic specimens with nonlinear behavior is predicted adopting a novel combination of the Equivalent Material Concept (EMC) and the Virtual Isotropic Material Concept (VIMC) in conjunction with the brittle failure criteria. By applying the EMC, the orthotropic material with nonlinear behavior is equated with a virtual linear one. Subsequently, using the VIMC, the orthotropic material with linear behavior obtained from the previous step is equated with a virtual isotropic material with linear behavior. Eventually, the load bearing capacity of the orthotropic nonlinear notched samples is predicted using two common brittle failure criteria, so-called the point stress criterion and the mean stress criterion. It is shown that both criteria employed for predicting the notch fracture toughness of the wood specimens are of good accuracy.